Analysis of Phonological Errors in Outdoor Media in Kediri Regency - Hesti Istikomah; Sujarwoko; Moch. Muarifin (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
The purpose of this study is to describe the analysis of language errors in outdoor media such as shop signs, billboards, banners found in Kediri Regency. This study uses a qualitative descriptive research method with three stages of the pre-research process, namely (1) preparation stage, (2) implementation stage, (3) completion stage. Forms of language errors were found with 59 data on writing errors, 7 data on punctuation errors, 6 data on letter usage errors, a total of 72 data. Then language errors were found in the type of shop signboard media 43 data, billboards 15 data, pamphlets 14 data. From all of the data, the results of the study were dominated by the most errors found in the type of shop signboard media and the most dominant form of language errors found was writing error data. From the data findings, it turns out that awareness to be able to refer to good and correct writing is still lacking. Keywords: Language,language errors, outdoor media